Parents of children diagnosed with cancer: work situation and sick leave, a five-year post end-of-treatment or a child's death follow-up study. (2nd October 2016) - Wikman, Anna; Hovén, Emma; Cernvall, Martin; Ljungman, Gustaf; Ljungman, Lisa; von Essen, Louise
Abstract: Background: Cancer in a child is associated with a significant impact on parental employment. We assessed the proportions of parents of survivors and bereaved parents working and reporting sick leave five years after end of successful treatment (ST)/child's death (T7) compared with one year after end of ST/child's death (T6) and the association between partial post-traumatic stress disorder (PTSD) and work situation and sick leave at T7. Participants and procedure: The sample included 152 parents of survivors (77 mothers, 75 fathers) and 42 bereaved parents (22 mothers, 20 fathers) of children diagnosed with cancer in Sweden. Results: The proportions of parents working or reporting sick leave did not differ among mothers and fathers of survivors (92% vs. 96% working, 20% vs. 18% on sick leave) or among bereaved mothers and fathers (91% vs. 90% working, 14% vs. 20% on sick leave) at T7. There was no change from T6 to T7 in the proportion of fathers working (fathers of survivors 91% vs. 96%, bereaved fathers 95% vs. 90%). Although more mothers of survivors (92% vs. 82%) and bereaved mothers (91% vs. 77%) worked at T7 than at T6, this increase was not significant. Fewer bereaved mothers reported sick leave at T7 than at T6 (14% vs. 59%, p < 0.05). Although more fathers reported sick leave at T7 than at T6 (fathers of survivors 18% vs. 8%, bereaved fathers 20% vs. 15%), this was not significant. Partial PTSD was not associated with parents' work situation or sick leave at T7. Conclusion: Results suggest little adverse effect on work situation and sick leave among parents of survivors and bereaved parents five years after end of ST/child's death from cancer. However, the pattern of change observed differed between parents, which could potentially indicate possible delayed consequences for fathers not captured in the present paper.